2022
DOI: 10.18122/ijpah.1.2.20.boisestate
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Procrastination and Exercise Behavior Among College Students

Abstract: Procrastination is prevalent in the study and life of the college student population. There is evidence suggesting that procrastination can have a negative impact on mood and behavior. However, in the field of exercise, the effects and mechanisms of procrastination on exercise have not been widely studied. Therefore, this study investigates the relationship between procrastination and exercise volume of college students, and discusses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been found that procrastination is negatively related to physical activity (Tao et al, 2022 ). Procrastination affects college students' physical activity through time efficiency (Zhang Y. et al, 2022 ). Research on academic procrastination has shown that physical activity interventions reduce academic procrastination (Li et al, 2022 ), and physical activity influences their depressive symptoms through the mediation of academic procrastination (Yang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that procrastination is negatively related to physical activity (Tao et al, 2022 ). Procrastination affects college students' physical activity through time efficiency (Zhang Y. et al, 2022 ). Research on academic procrastination has shown that physical activity interventions reduce academic procrastination (Li et al, 2022 ), and physical activity influences their depressive symptoms through the mediation of academic procrastination (Yang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%